Paediatric low speed vehicle run-over fatalities in Queensland. (27th January 2011) - Griffin, Bronwyn; Watt, Kerrianne; Wallis, Belinda; Shields, Linda; Kimble, Roy
Abstract : Introduction: Child pedestrian fatalities associated with motor vehicles reversing or moving at low speed are difficult to identify in surveillance data. This study aims to determine the incidence of fatalities associated with what is thought to be an under-reported and preventable fatal injury mechanism. Methods: The term low speed vehicle run-over (LSVRO) incidents encompasses pedestrian fatalities where vehicles run-over a child at low speed. Data were obtained for children aged 0–15 years in the Australian state of Queensland (January 2004–December 2008). Results: There were 15 deaths (12 boys and 3 girls) during 2004–2008 (rate:1.67/100 000). Over half were aged 0 and 1 years of age (n=8; 53.3%, rate: 14.67/100 000), and one quarter were 2 and 3 years of age (n=4, 27%, rate 7.46/100 000). There were no LSVRO deaths recorded among 10–15 year olds. Most (13/15) of the incidents occurred on private property, and only two occurred on a street/road. Almost half of the fatalities were caused by a four wheel drive (4WD) vehicle; large family sedans were involved in four fatalities, and heavy vehicles were involved in three deaths. In 11 of the fatalities, parents were the drivers of the vehicle involved (mothers 5; fathers 6). In nine, the vehicle involved was reversing before it came in contact with the child. Fatalities occurred in each of the Socio-Economic Indexes For Areas (SEIFA) levels. Conclusion: The unique data provided by the child death review team has signalled that LSVRO fatalities are a significant problem in Queensland. The Commission for Children and Young People and Child Guardian (CCYPCG) continue to collect data, which, when combined, will provide outcomes that will act as an impetus for promoting intervention and child advocacy.